2019
DOI: 10.20473/jn.v14i1.9664
|View full text |Cite
|
Sign up to set email alerts
|

Caring Efficacy and Nurse Caring Behavior in Taking Care of Critical Patients

Abstract: Introduction: Critical patients have different needs compared to patients in other general inpatient wards, so they need extra treatments from a nurse. Nurse caring behavior gived through an approach in which nurses work by improving their concern to patients. However, it is influenced by caring efficacy in which a nurse is confident to express his or her caring to patients. The aims of this study were to identify the correlation between caring efficacy with nurse caring behavior in taking care of critical pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…It is also supported by Riani 33 theory explanations that the length of the working period does not guarantee working productivity even for nurses. Otherwise, Lukmanulhakim 27 confirmed that the presence of nurses' caring behavior is affected by the working period they are experienced. It revealed that after approximately 7 years of giving caring services, nurses tend to recognize their patients' background deeper, and then can increase their caring behavior quality 26,27 .…”
Section: Working Years Towards Caring Behaviormentioning
confidence: 95%
See 2 more Smart Citations
“…It is also supported by Riani 33 theory explanations that the length of the working period does not guarantee working productivity even for nurses. Otherwise, Lukmanulhakim 27 confirmed that the presence of nurses' caring behavior is affected by the working period they are experienced. It revealed that after approximately 7 years of giving caring services, nurses tend to recognize their patients' background deeper, and then can increase their caring behavior quality 26,27 .…”
Section: Working Years Towards Caring Behaviormentioning
confidence: 95%
“…Otherwise, Lukmanulhakim 27 confirmed that the presence of nurses' caring behavior is affected by the working period they are experienced. It revealed that after approximately 7 years of giving caring services, nurses tend to recognize their patients' background deeper, and then can increase their caring behavior quality 26,27 . Nevertheless, we assume that when a nurse experiences longer working years and sufficient working skills, it depends on supported facilities, working atmosphere, and motivation enhanced.…”
Section: Working Years Towards Caring Behaviormentioning
confidence: 95%
See 1 more Smart Citation
“…Given that nursing is an ethical profession, nurses have a significant impact on patient satisfaction through the caring behaviors they provide. Although nurses' adherence to caring behaviors principles while providing care protects patient safety and promotes faster recovery, researches illustrate that nurses do not adhere to caring behaviors when providing care (Bijani et al, 2017;Lukmanulhakim et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Caring in acute and critical care rooms has a more complex and dynamic nature due to unstable patient conditions and requires more attention from nurses (Biswas et al, 2016;Lukmanulhakim et al, 2019). Acute and critical care environments concentrate physiological needs and employ a variety of medical treatments and interventions, putting a high demand on technological competency from health practitioners (Locsin, 1999).…”
Section: Introductionmentioning
confidence: 99%